Frictionless mobility of submicron particles in model viscid fluid. (6th February 2019) - Stanek, J; Fornal, P; Dziedzic-Kocurek, K
Abstract: The mechanism of inter- and intracellular diffusional transport by vesicles in living organisms is poorly understood at the molecular scale. The diffusion of submicron and nanoparticles in dense media has been treated by numerous theoretical models. We face this problem experimentally using Mössbauer spectroscopy. On a characteristic for this method narrow time scale (≈10 −7 s), the velocity distribution of 120 nm spherical Fe2 O3 particles suspended in a 60% water solution of sucrose was determined by analyzing the 57 Fe Mössbauer spectral line profile. The particles usually exhibit classical Brownian motion, but their main diffusion mechanism is related to infrequent ( f ≈ 10 6 s −1 ) but distant ( d ≈ 1 nm) translations. During such movements, the particles experience a minimal friction described by the temporal local viscosity, η loc ≈ 28 μ Pa·s.